Future Teachers’ Environmental Stance and Teaching: Cultivating Eco-Conscious Educators - Ranjan, Rajeev (Journal of Advanced Research in English & Education, 2024)
This article explores the crucial role of future teachers’ environmental stance in shaping their pedagogical approaches and ultimately influencing the environmental literacy and values of their students. In an era of increasing environmental challenges, educators hold a significant responsibility in fostering a generation that is environmentally aware, responsible, and empowered to act. This paper argues that teacher education programmes must actively cultivate a strong positive environmental stance among pre-service teachers, equipping them with the knowledge, skills, and dispositions to integrate environmental themes effectively into their teaching practices across various subjects. The article outlines ten key areas that need to be addressed within teacher education to achieve this goal. These areas include developing a deep understanding of environmental issues, fostering pro environmental attitudes and values, promoting pedagogical approaches for environmental education, integrating sustainability across the curriculum, building partnerships for environmental action, utilizing technology for environmental learning, developing critical thinking skills for environmental problem-solving, fostering emotional connections with nature, addressing environmental justice and equity, and promoting reflective practice on environmental teaching. By focusing on these aspects, teacher education can empower future educators to become effective agents of environmental change, nurturing environmentally responsible citizens who are equipped to address the challenges of the 21st century.